(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
One Hundred Bottles (Ena Lucía Portela, 2002) presents a range of characters living on the margins of society in Havana during the 1990s and early 2000s. Here, I will analyse the character La Gofia, a mixed-race lesbian dancer with a punk aesthetic, who hosts sexually inclusive, illegal parties. Drawing on feminist and queer theory, and incorporating race relations in Cuba, I will use Portela’s novel to shed light on both the Cuban cultural hegemonies which render people like La Gofia the ‘Other’, and how the character challenges and destabilises said structures to carve out space for herself and her community.